Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T18:35:32+01:00
1.
a)(2x² + 4x - 3) + ( -x² - 2x +4)=
=2x² + 4x - 3 -x² -2x + 4 =
=x² + 2x + 1
b) (⅗m² + ⅔n² + 6) + (-⅓m² - ⅔n² - 2⅗)=
=⅗m² + ⅔n² + 6 - ⅓m² - ⅔n² - 2⅗=
=⅖m² + 3⅖
c) (0,5xy² - 1,2y² + 5) + (-0,8y² - 2,5xy² - 2⅛)=
= 0,5xy² - 1,2y² + 5 - 0,8y² - 2,5xy² -2⅛=
= -2xy² - 2y² + 2⅞
2.
a) (6a² + 2a + 1) - (-3a² - 2a +5)=
=6a² + 2a + 1 + 3a² + 2a - 5=
=9a² + 4a -4
b) (12½m² - 1¼n² -1,6) - (2¼m² + 3¾n² + 2,4)=
=12½m² - 1¼n² - 1,6 - 2¼m² - 3¾n² -2,4=
=10¼m² - 5n² - 4
c) (1,5x²y - ¾x² - 15) - (⅖x²y - 2⅔ - ⅛x²=
=1,5x²y - ¾x² - 15 - ⅖x²y + 2⅔ + ⅛x²=
=⅕x²y - ⅝x² - 12⅓
2010-03-12T18:36:49+01:00
A)
(2x² + 4x - 3) + ( -x² - 2x +4)=
=2x² + 4x - 3 -x² -2x + 4 =
=x² + 2x + 1
b)
(⅗m² + ⅔n² + 6) + (-⅓m² - ⅔n² - 2⅗)=
=⅗m² + ⅔n² + 6 - ⅓m² - ⅔n² - 2⅗=
=⅖m² + 3⅖
c)
(0,5xy² - 1,2y² + 5) + (-0,8y² - 2,5xy² - 2⅛)=
= 0,5xy² - 1,2y² + 5 - 0,8y² - 2,5xy² -2⅛=
= -2xy² - 2y² + 2⅞




2.
a)
(6a² + 2a + 1) - (-3a² - 2a +5)=
=6a² + 2a + 1 + 3a² + 2a - 5=
=9a² + 4a -4
b)
(12½m² - 1¼n² -1,6) - (2¼m² + 3¾n² + 2,4)=
=12½m² - 1¼n² - 1,6 - 2¼m² - 3¾n² -2,4=
=10¼m² - 5n² - 4
c)
(1,5x²y - ¾x² - 15) - (⅖x²y - 2⅔ - ⅛x²=
=1,5x²y - ¾x² - 15 - ⅖x²y + 2⅔ + ⅛x²=
=⅕x²y - ⅝x² - 12⅓